PENERAPAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION DALAM MENINGKATKAN HASIL BELAJAR SISWA - Dudu Suhandi Saputra; Yuyu Yuliati; Dadan Arif Hidayat (Jurnal Numeracy, 2019)
This research is motivated by the low student learning outcomes in Mathematics. This study aims to improve the learning outcomes of grade IV students at SDN Jayi I through the application of the Realistic Mathematic Education approach. The subject of this study was the fourth-grade students of SDN Jayi I as many as 24 students consisting of 13 female students and 11 male students. Data collection techniques used are tests, observations, interviews, field notes and documentation. This research was conducted in 3 cycles with 3 actions in each cycle. The results of the study show that the application of the Realistic Mathematic Education approach can improve student learning outcomes. This is indicated by an increase in the average value from before giving the action to the third cycle. The average value obtained in the first cycle reached 56.70 with a graduation percentage of 37.5%. In the second cycle the average value obtained increased to 66.33 with a graduation percentage of 62.5%. In the third cycle the average value obtained increased to 71.66 with a graduation percentage of 79.7%. In general, it can be concluded that the application of the Realistic Mathematic Education approach can improve student learning outcomes in Mathematics in the fourth grade of Jayi I Elementary School, Sukahaji District, Majalengka District. Abstrak Penelitian ini dilatarbelakangi masih rendahnya hasil belajar siswa pada mata pelajaran Matematika. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa kelas IV di SDN Jayi I melalui penerapan pendekatan Realistic Mathematic Education. Subjek penelitian ini adalah siswa kelas IV SDN Jayi I sebanyak 24 siswa yang terdiri dari 13 siswa perempuan dan 11 siswa laki-laki. Teknik pengumpulan data yang digunakan adalah tes, observasi, wawancara, catatan lapangan dan dokumentasi. Penelitian ini dilaksanakan dalam 3 siklus dengan 3 tindakan pada tiap siklusnya. Hasil penelitian menunjukan bahwa penerapan pendekatan Realistic Mathematic Education dapat meningkatkan hasil belajar siswa. Hal ini ditunjukan dengan adanya peningkatan nilai rata-rata dari sebelum pemberian tindakan sampai dengan siklus III. Nilai rata-rata yang diperoleh pada siklus I mencapai 56,70 dengan presentase kelulusan 37,5%. Pada siklus II nilai rata-rata yang diperoleh meningkat menjadi 66,33 dengan persentase kelulusan 62,5%. Pada siklus III nilai rata-rata yang diperoleh meningkat menjadi 71,66 dengan persentase kelulusan 79,7%. Secara umum dapat disimpulkan bahwa penerapan pendekatan Realistic Mathematic Education dapat meningkatkan hasil belajar siswa pada pelajaran Matematika di kelas IV SDN Jayi I Kecamatan Sukahaji Kabupaten Majalengka. Kata Kunci: Hasil Belajar Siswa, Pendekatan Realistic Mathematic Education